Chalcogenide Glass Hollow-Core Microstructured Optical Fibers - Shiryaev, Vladimir S. (Frontiers in Materials, 2015)
The recent developments on chalcogenide glass hollow-core microstructured optical fibers (HC-MOFs) are presented. The comparative analysis of simulated optical properties for chalcogenide HC-MOFs of negative curvature with different size and number of capillaries is given. The technique for the manufacture of microstructured chalcogenide preforms, which includes the assembly of the substrate glass tube and 8–10 capillaries, is described. Further trends to improve the optical transmission in chalcogenide negative curvature hollow-core photonic crystal fibers are considered.